2023
DOI: 10.1002/ejlt.202200120
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Measure Cell to Assess by Amperometry Dissolved Oxygen in Vegetable Oils

Abstract: Dissolved oxygen in vegetable oils is an important component of oil degradation over time. Various methods for the determination of dissolved oxygen in oils are proposed in the literature leading to very variable results. An amperometric method associated with a cell of measurement in dynamic mode makes it possible to determine the conditions of stability of the measurements of the relative dissolved oxygen concentration (RDOC, mg L −1 ) and the electrolysis current intensity (ECI) (nA) in seed oils and virgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Moreover, the authors showed that the extent of the mechanical action applied during the oil extraction does not allow to reach the theoretical solubility value of oxygen in the oil. Accordingly, the maximum DO concentration recorded in that work was of about 8-9 mg L -1 , close to the values of Ninfali et al, [16] as well as the highest values reported by Fakhri et al [15] Interestingly, the latter authors This is in agreement with Parenti et al, [20] which found a faster oxidative decay of VOO with a greater initial content of DO during a controlled 18 months storage.…”
Section: F I G U R Esupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, the authors showed that the extent of the mechanical action applied during the oil extraction does not allow to reach the theoretical solubility value of oxygen in the oil. Accordingly, the maximum DO concentration recorded in that work was of about 8-9 mg L -1 , close to the values of Ninfali et al, [16] as well as the highest values reported by Fakhri et al [15] Interestingly, the latter authors This is in agreement with Parenti et al, [20] which found a faster oxidative decay of VOO with a greater initial content of DO during a controlled 18 months storage.…”
Section: F I G U R Esupporting
confidence: 91%
“…These data fit well with the results reported by Ninfali et al, [16] where DO values ranged from 2 to 7 mg L -1 in bottled VOO samples collected from the market. Fakhri et al [15] measured substantially lower DO concentrations in VOO samples stored for several weeks in unopened bottles, with values ranging from 0 to 0.9 mg L -1 . This finding is corroborating because of the expected inverse relationship between oxygen solubility and temperature, also confirmed by Fakhri et al [15] The next step in data analysis has been the application of a general linear model where the source of variation are both the unit-operation factor (7 levels) and the operation-effect (2 levels), and their interaction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations